The Role of Transformational Leadership and Employee Competence inEnhancing Talent Employee Quality in the Automotive Parts Industry - Slamet Ardyanto; H. M. Sidik Priadana; Erni Rusyani (Pelopor Publikasi Akademika, 2026)
Talent employee quality is a strategic concern in automotive parts manufacturing because this industry requires precision, quality compliance, production reliability, and adaptability to technological change. This research examines the role of transformational leadership and employee competence in enhancing talent employee quality among permanent employees of automotive parts manufacturing companies in Bekasi, Karawang, and Purwakarta, Indonesia. The research used a quantitative descriptive-verificative design. The population consisted of 20,219 permanent employees from 14 companies, and 400 respondents were selected through cluster proportional random sampling. Data were collected using an ordinal-scale questionnaire and analyzed through descriptive statistics, measurement-model evaluation, reliability assessment, and structural equation modeling with LISREL 8.80. The results show that transformational leadership has a positive and significant effect on talent employee quality (path coefficient = 0.2816; t = 5.1176), while employee competence also has a positive and significant effect (path coefficient = 0.2526; t = 4.5843). Both t-values exceed the critical value of 1.9660 at the 5% significance level. The full antecedent block in the original SEM model explained 75.55% of the variance in talent employee quality. The study contributes to human resource management literature by positioning talent employee quality as a construct shaped by organizational leadership and individual competence in a manufacturing context.